Solution-Focused Brief Group Counseling (SFGC) Untuk Meningkatkan Self-Acceptance Pada Anak Korban Perceraian - Sri Ayatina Hayati; Aminah Aminah (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2020)
The objectives to be achieved in this research are to find out how big the Self Acceptance of Broken Home students is before getting the Solution-Focused Brief Group Counseling approach at MTs Al-Ikhwan Banjarmasin, to find out how much influence Solution-Focused Brief Group Counseling has to increase the Self Acceptance of Broken children. Home at MTs Al-Ikhwan Banjarmasin, and To find out how effective Solution-Focused Brief Group Counseling is to increase the Self Acceptance of Broken Home children at MTs Al-Ikhwan Banjarmasin. The type of research used is experimental research (non parametric). The results of the study on the level of self-acceptance of broken home students before getting the Solution-Focused Brief Group Counseling approach at MTs Al-Ikhwan Banjarmasin were in low categorization. The increase in self-acceptance of children with broken homes through a solution-focused brief group counseling approach is evenly distributed, in other words, pre-test data has a significant relationship/influence with post-test data.